Knowledge attitude and practice towards human papilloma virus vaccination among medical and paramedical students in a tertiary care teaching hospital in south Karnataka, India - B., Shruthi; Mallam, Srikanth Goud; K., Manojkumar B.; A., Dhanalakshmi T. (International Journal of Advances in Medicine, 2019)
Background: Human papilloma virus infection is responsible for 75-80% of the cervical cancers worldwide. Human papilloma virus infection is a preventable disease, but precaution depends on the cognitive aspects of young women. Authors conducted a study to assess the knowledge, attitude and practices regarding human papilloma virus vaccination and to determine acceptance rate of human papilloma virus vaccination among medical and paramedical students. Methods: Human papilloma virus infection is responsible for 75-80% of the cervical cancers worldwide. Human papilloma virus infection is a preventable disease, but precaution depends on the cognitive aspects of young women. Authors conducted a study to assess the knowledge, attitude and practices regarding human papilloma virus vaccination and to determine acceptance rate of human papilloma virus vaccination among medical and paramedical students. Results: Out of 322 students, 114 medicals (35.4%), 106 pharmacy (32.9%) and 102 nursing students (31.7%) were included in this study. Ninety-one (79.8%) medical students, 64 (60.37%) pharmacy students, 43 (42.1%) nursing students were aware that human papilloma virus can cause cervical cancer. Seventy-three (64.03%) medical students, 64(60.37%) pharmacy students, 40(40.1%) nursing students were aware that there is vaccination for human papilloma virus infection, and it can prevent cervical cancer. Most of the students,78(68.4%) medical students, 57 (53.77%) pharmacy students and 46(45.09%) nursing students believe that more awareness required regarding risk factors of human papilloma virus infection and prevention of cervical cancer. Furthermore, around 66 (57.89%) medical students, 44 (41.05%) pharmacy students, 37(36.27%) nursing students were willing to accept the vaccine for themselves. Conclusions: Majority of the students are lacking knowledge regarding HPV vaccination and cervical cancer prevention with least knowledge among paramedical students. More awareness programmes are required to increase the awareness and acceptability of HPV vaccination.